Principles of athletic training a guide to evidence-based clinical practice - Prentice, William E. (New York, NY McGraw-Hill Education, 2017)
Principles of athletic training: a competency-based approach is designed to be used by athletic trainers in courses concerned with the scientific, evidence-based and clinical foundations of athletic training and sports medicine. The text leads the student from general foundations to specific concepts relative to injury prevention, evaluation, management, and rehabilitation.
Pt. I. Professional development and responsibilities. Ch.1. The athletic trainer as a health care provider ; Ch.2. Health care organization and administration in athletic training ; Ch. 3. Legal concerns and insurance issues -- Pt. II. Risk management. Ch. 4. Fitness and conditioning techniques ; Ch. 5. Nutrition and supplements ; Ch. 6. Environmental considerations ; Ch. 7. Protective equipment ; Ch. 8. Wrapping and taping -- Pt. III. Pathology of sports injury. Ch. 9. Mechanisms and characteristics of musculoskeletal and nerve trauma ; Ch. 10. Tissue response to injury -- Pt. IV. Management skills. Ch. 11. Psychosocial intervention for sports injuries and illnesses ; Ch. 12. On-the-field acute care and emergency procedures ; Ch. 13. Off-the-field injury ; Ch. 14. Infectious diseases, bloodborne pathogens, and universal precautions ; Ch. 15. Using therapeutic modalities ; Ch. 16. Using therapeutic exercise in rehabilitation ; Ch. 17. Pharmacology, drugs, and sports -- Pt. V. Musculoskeletal conditions. Ch.18. The foot ; Ch. 19. The ankle and lower leg ; Ch. 20. The knee and related structures ; Ch. 21. The thigh, hip, groin, and pelvis ; Ch. 22. The shoulder complex ; Ch. 23. The elbow ; Ch. 24. The forearm, wrist, hand, and fingers ; Ch. 25. The spine -- Pt. Vi. General medical conditions. Ch. 26. The head, face, eyes, ears, nose, and throat ; Ch. 27. The thorax and abdomen ; Ch. 28. Skin disorders ; Ch. 29. Additional general medical conditions -- Appendixes
Subtitle changed from previous edition.
Includes bibliographical references and index.
Keywords: Athletic trainers; Physical education and training